Prioritizing and Actualizing Academic users’ Satisfaction on Quality Library Services in University Libraries of Haryana - Mithu Dey, Satish Kumar (International Journal of Advanced Science and Technology, 2020)
The preeminent objective of the research paper was to recognize the service quality gaps by using SERVQUAL instrument on university libraries of Haryana and to advise appropriate strategies for attaining the remarkable service quality for satisfying the informational needs of existing and prospective library users. To evaluate the rate of success and offering quality library services to its entire target users is prevalent importance of university libraries. A quality library service is an effective tool to attract the library users. The level of service can be measured by obtaining the difference between the perceived library services and users’ expectations. A modified SERVQUAL instrument was used for this study. The results of the survey analysis illustrated a discrepancy in the quality of the services delivered by the library and those expected by the library users. Keyword: SERVQUAL, service quality, library services, library users, university libraries, Haryana.